A new sand adsorbent for the removal and reuse of nickel ions from aqueous solutions - Tao, Wenhong (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
Nickel ions (Ni(II)) in aqueous solutions were removed by a sand adsorbent with a surface functionalized porous coating. The sand adsorbent has a very large surface area of 150 m2/g. The influence of pH, initial concentration of the solution, temperature, contact time and adsorbent dosage on the removal efficiency of the synthesized sand adsorbent toward Ni(II) in the aqueous solutions were studied. The results indicate that the adsorption of nickel onto the sand adsorbent greatly increases the pH range of 2-4 and slightly increases with temperature from 25 to 40 °C. The maximum removal efficiency and ion retention in per unit mass of the adsorbent were 100% and 5.78 mg/g, respectively, under the specified experimental conditions. The adsorption can be described by the pseudo-second-order kinetic model and the Freundlich adsorption model. The adsorbed nickel (4.24 mg/g) together with the spent adsorbent were successfully employed to prepare a brown glass, suggesting a new way to reutilize the recovered nickel from wastewater and to avoid secondary pollution caused by the used adsorbents